ANALISIS EFISIENSI PRODUKSI DAN STRUKTUR BIAYA PADA USAHATANI NANAS DI DESA ASTOMULYO KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Aji Prayoga Wibowo; Wan Abbas Zakaria; Dyah Aring Hepiana Lestari (Lampung University, 2021)
This study purposes are to analyze factors that affect production of pineapple farming, production efficiency of pineapple farming, and cost structure of pineapple farming. Data were collected at Astomulyo Village Punggur Subdistrict Central Lampung Regency in December 2019 – February 2020. The number of respondents was 63 farmers consisting of 58 farmers who were members of farmer groups and the rest were non-members of farmer groups by using simple random sampling. The primary data were obtained from direct interview with the pineapple farmers and the secondary data were obtained from several related studies and institutions. The data were analyzed using Stochastic Frontier production function. The study shows the factors affecting the production of pineapple farming are land area, C/N ratio, N element, and P element. The pineapple farming is technically, allocatively, and economically efficient yet. The biggest costs on pineapple farming are costs of seed, land lease, and labor.Key words: costs, efficiency, farmers, pineapple